Perlindungan Hukum Terhadap Anak Korban Eksploitasi Seksual Melalui Media Video Call - Chasanah, Kania Amru (Proceedings Series on Social Sciences & Humanities, 2024)
Children are the embryo of the birth of a new generation which is the successor to the ideals of the nation's struggle and human resources for national development. Children are national assets, the future of the nation and state in the future is in the hands of children now. "The better the child's personality now, the better the future life of the nation will be. Likewise, if the child's personality is bad, the future life of the nation will be bad. Crimes against decency in general raise concern, especially parents' anxiety for female children because apart from being able to threaten the safety of female children (for example rape, obscene acts) they can also affect the process of growth towards earlier sexual maturity. This research discusses 2 ( two) things, namely the urgency of anti-sexual crime education in tackling sexual crimes against children and legal protection for children who are victims of sexual crimes. A brief conclusion can be drawn from this discussion, namely that sexual education/anti-sexual crimes are very important and necessary to introduce every child to know and understand which parts of the body organs should not be touched by other people. Apart from that, legal protection for children as victims has been accommodated in several laws and regulations, especially in Law Number 35 of 2014 Jo. Law Number 23 of 2002 concerning Child Protection.